Synthesis and characterization of magnetic nanoparticles coated with poly aniline for removal of 2,4-dinitrophenol / Shuhaili Rashid - Rashid, Shuhaili (Faculty of Applied Sciences, 2017)
Magnetic nanoparticles ( MNPs) coated polyaniline (P ANI) was successfully synthesized and further used for removal of 2.4-dinitrophenol. The presence of PANI coatings on the surface of MNPs was confirmed by using Fourier Transform Infrared (FT-IR) Spectroscopy. Scanning Electron Microscopy (SEM) and X-ray Diffractometry (XRD) analysis. MNPs coated PANI (MNPs/PANI) showed higher capabilities to remove 2,4- dinitrophenol (2.4-DNP) via spectrophotometry at 358 nm by using Ultraviolet Visible (UV-Vis) Spectrophotometer. Different parameters such as pH, contact time, initial concentration and temperature, amount of adsorbent, interfering ions were investigated to optimize the performance of MNPs/P ANI in removal of 2,4-DNP. In addition, the reusabilities of MNPs/P ANI was also studied to add up its economic value. The best perfonnance of MNPs/P ANI to remove 2,4-DNP molecules was found at pH 7, I 05 minutes contact time, IO ppm initial concentration of 2,4-DNP with 298.15 K temperature and I 0 mg of adsorbent amount. The percentage removal (¾R) of 2,4-DNP was still up to 90% in the presence of chloride (Cl-) ions, nitrate (NO3-) ions and sulfate (SO42-) ions. Lastly MNPs/P ANI was used up to five cycles.